Revisiting the Originality of Indonesian Philosophy (Indonesian Humankind and Philosophical Identity) - Susanto, Anthon Freddy; Pratama, Mohammad Alvi (Տիգրան Մեծ)
In the Indonesian context, philosophy is described as human philosophy, which attempts to reflect and bring together basic and complicated concepts about humans and the surrounding life. Indonesian Philosophy is articulated by at least three meanings. To begin, Indonesian are evaluated via Western interpretations, notably colonialization, for the advantage of the West. The second perspective, views Indonesians through the lens of indigenous knowledge who develop a fighting spirit to escape oppression, this perspective has objective resistance and freedom from colonialism.The third perspective integrates Western and indigenous Indonesian philosophy, notably by integrating what is deemed beneficial in the West with indigenous Indonesian concepts. Indonesian people are viewed through their traditional lens and progress during the globalization and digitization era. Indonesian are described as imaginative individuals who possess cognitive, emotional and spiritual intelligence.The discussion of Indonesian philosophy as a separate identity involves three fundamental interconnected topics: Indonesian human conceptions, Indonesian culture, and Indonesian thoughts or souls. The description of Indonesian is the most difficult to explain because this description is not only about physical structures, the brain and intelligence, but also about how personality, life, oneness with nature, and merging chages of Indonesians can be distinguished from those of other.
Keywords: Indonesian philosophy